Endometrial receptivity change: ultrasound evaluation on ovulation day and transplantation day during the natural frozen embryo transfer cycle - Li, Xihong; Peng, Yangqin; Mao, Yuyao; Li, Yuan; Gong, Fei; Ouyang, Yan (Frontiers in Endocrinology, 2023)
Objective: To obtain quantitative and comprehensive results of the changes in comprehensive ER indicators from ovulation day to transplantation day by ultrasonography during the natural frozen-thawed embryo transfer cycle (FET). Methods: This is a prospective analysis of 230 infertile women undergoing their first FET cycles from April 2019 to July 2021. To evaluate ER, ultrasound scans were performed on the days of ovulation and embryo transfer for all included patients. All included patients were divided into a pregnancy group and a nonpregnancy group according to whether clinical pregnancy was achieved. The ER changes from ovulation day to transplantation day in the overall study population (n=230), pregnancy group (n=158) and nonpregnancy group (n=72) were analyzed. Results: In the overall population, type C was predominant on ovulation day, but type B was the most common on transplantation day (P<0.001). From ovulation day to transplantation day, endometrial thickness was significantly increased (11.26±2.14 vs. 11.89±2.08 mm, P<0.001), but endometrial volume (4.26±1.75 vs. 4.03±1.62 ml, P<0.001), endometrial VI (1.34±1.64 vs. 0.95±1.99, P<0.001), VFI (0.47±0.72 vs. 0.4±1.03, P<0.001), subendometrial VI (5.04±3.89 vs. 3.29±2.92, P<0.001), FI (34.07±4.61 vs. 33.41±5.3, p=0.004), VFI (2.07±2.65 vs. 1.19±1.19, P<0.001) and frequency of endometrial peristalsis (2.9±1.44 vs. 1.4±1.41, P<0.001) were significantly decreased. In the pregnancy group, the changes in all ultrasound parameters were in the same direction as those in the overall population. In the nonpregnancy group, except for endometrial volume and VI, which showed no difference, other ultrasound parameters showed the same direction of change as those in the overall population. No significant difference was found in the pregnancy probability among the different absolute change groups. Conclusion: During a natural cycle, the morphology of the endometrium changes mostly from type C to type B, the endometrial thickness increases, and the volume decreases. The blood supply of the endometrium, the subendometrial 5 mm and the frequency of peristalsis decrease from ovulation day to transplantation day. Compared with the nonpregnancy group, the pregnancy group tended to have more obvious decreases in endometrial volume and blood flow perfusion. However, these endometrial changes do not mean that pregnancy is bound to occur.